Atomic Middle Power: Canada’s Nuclear Export and Non-Proliferation Policy - Khazaeli, Susan (Université d'Ottawa / University of Ottawa, 2018)
This dissertation examines Canada’s nuclear export and non-proliferation policy. It demonstrates that contrary to the received wisdom on nuclear behaviour, Canada does not think ‘strategically’ in the nuclear field. I argue that while the decision-making of great powers may be straightforward in the nuclear field, non-great powers can afford to be more ambivalent and even less cautious. The focus of the dissertation is on Canada’s nuclear export decisions from the 1950s to the late 1970s. My contention is that middle powers, like Canada, are rarely influenced by military-strategic interests, but that they, nonetheless, act according to their own particular self-interests when determining whether or not to export nuclear materials and technology. In looking at Canada’s nuclear decision-making from its entry into the nuclear age until the late 1970s, the dissertation offers three findings. First, Canada does not make decisions that fit a military-strategic calculus. Second, Canada is often ambivalent in the nuclear field. I argue that Canada can afford to be ambivalent because constraints on its decision-making do not stem primarily from security concerns or existential threats but from beliefs as to what Canada should do and should be in global affairs. Finally, Canada’s nuclear export and non-proliferation policies have been defined primarily by its place – both real and imagined – in the world as a middle power. The argument rests on insights draw from liberal IR theory as well as domestic politics explanations of nuclear behaviour. My contention is that Canada’s decision-making has been influenced by domestically held beliefs and perceptions of its identity – that is, where Canada ranks on the figurative power spectrum and what values it professes in relation to other actors in the international system. My research thus makes a contribution to the literature on nuclear supply and on the broader literature on nuclear behaviour, more generally.
Keywords: international relations; international security; Canadian foreign policy; nuclear proliferation; nuclear cooperation; middle power